Development of a Guided Inquiry-Based Moodle E-Learning System on the Topic of Salt Hydrolysis - Sari, Mutia Ulan; Mawardi, Mawardi (Jurnal Pendidikan MIPA, 2022)
The goal of this research to develop a guided inquiry-based flipped classroom learning system using Moodle on the topic of salt hydrolysis and determine the level of validity and practicality of the resulting learning system. This research is included in the Educational Design Research research with the Plomp development model. The research subjects were material experts, media experts, chemistry teachers, and students of class XII science at SMAN 8 Padang. The results of this study indicate that the learning system developed is valid with a validity value of 0.88 from material experts and 0.92 from media experts while for the percentage of practicality 92% of student responses and 94% of teacher responses with very practical categories so that it can be used as an alternative to online learning.Keywords: flipped classroom, guided inquiry, salt hydrolysisDOI: http://dx.doi.org/10.23960/jpmipa/v23i1.pp244-255